The Blood of a Prophet and the Conscience of a King. Issue 1 (2nd January 2017) - Williams, Owen
Abstract : In 1591, James VI of Scotland intervened on behalf of a convicted English Hebraist and minister, John Udall, during his sentencing trial for writing seditious tracts against Elizabeth and her bishops. Udall had advocated for a presbyterian church structure aligned with the Genevan Discipline, and his case was complicated by his involvement with the Marprelate controversy. After the Court of High Commission – with its notorious ex officio mero oath – failed to indict Udall, the common law courts swiftly convicted him. Despite the serious legal shortcomings in the Crown's case, however, James focused his defense on the premise that they were both sincere interpreters of prophetic scripture, or prophets, in one contemporary sense of the word. This episode thus offers a new perspective on James' complicated relationship with presbyterians more than a decade before his accession to the throne of England.